ByzRev 08.2026.012: Michael C. Paul, “Chosen By God”: The Archiepiscopal Office in Novgorod the Great (1165–1478).: Washington DC: New Academia Publishing 2025 - Vasselle, Pauline (The Byzantine Review, 2026)
Michael C. Paul, “Chosen By God”: The Archiepiscopal Office in Novgorod the Great (1165–1478). Washington DC: New Academia Publishing 2025. 501 pp. – ISBN 978-0-615-43269-4